Social action of syntactic reduplication - Keevallik, Leelo (Journal of pragmatics, 2010)
Reduplication has been shown to carry the semantic meaning of increased intensity, duration or emphasis. This study demonstrates that syntactic reduplication in Estonian is regularly used in responsive positions in action sequences. Instances of syntactic reduplication constitute specific social practices such as affiliative and disaffiliative urging, challenging the prior speaker, reinforcing answers to yes/no questions, and providing a non-elicited confirmation. Syntactic reduplication is a sedimented linguistic pattern grounded in the social actions it recurrently performs. Different reduplicative actions furthermore display characteristic prosodic features, involving initial prominence in affiliative actions and delayed pitch peak in disaffiliative ones. Mock repeats and disconfirming answers are produced with double pitch peaks. Grammar and prosody are complementary means of achieving social action in particular positions in interactive sequences. The paper shows that sequential and social contingencies may be essential in understanding a grammatical pattern.